PERGESERAN PRINSIP HAKIM PASIF KE AKTIF PADA PRAKTEK PERADILAN PERDATA PERSPEKTIF HUKUM PROGRESIF - Rian Saputra (Wacana Hukum, 2019)
This article aims to find out the views of progressive law regarding the shift in the principle of judges to civil justice. M. Yahya Harahap, described this as a symptom of the emergence of a new flow in the realm of civil procedural law that tried to oppose the idea of a total passive judge by trying to introduce the principle of an argumentative active judge. One form of activeness of judges in civil courts is the decision of a judge to judge a case that is not prosecuted or decide beyond what is requested (Ultra Petita Principle). Based on the provisions of Article 178 paragraph (3) HIR and Article 189 paragraph (3), the RBg petita Ultra is prohibited, so that the factie violating ultra petita is considered as an act that exceeds authority. This article uses normative research. This article explains the view of progressive law regarding the shift in principle to civil judges, namely the shift is appropriate, if it aims to seek justice for the parties to the dispute.